Diagnosis and control of polypharmacy in the elderly Diagnóstico e controle da polifarmácia no idoso - Patrícia Medeiros-Souza; Leopoldo Luiz dos Santos-Neto; Liana Tieko Evangelista Kusano; Maurício Gomes Pereira (Universidade de São Paulo, 2007)
The article had the purpose of commenting on studies on polypharmacy in the elderly, focusing on diagnosis and control. Polypharmacy is defined as the use of a number of medications at the same time and the use of additional drugs to correct drug adverse effects. The fact that the elderly take more medications for the treatment of several diseases makes them more susceptible to the occurrence of adverse reactions. Prophylactic actions such as balanced prescriptions are vital to reduce the incidence of these reactions and prevent longer hospital stay, increased costs and aggravation of the elderly health condition. O artigo teve por objetivo comentar estudos sobre polifarmácia em idosos, particularmente em diagnose e controle. O conceito de polifarmácia considera o uso de diversos medicamentos ao mesmo tempo, além da utilização de um fármaco para corrigir o efeito adverso de outro. Por consumirem mais medicamentos para o tratamento de diversas doenças, os idosos são mais vulneráveis ao surgimento de reações adversas. Medidas profiláticas, como a prescrição balanceada, são de fundamental importância para diminuir essas reações, tendo em vista o aumento do tempo de internação, gasto e piora do quadro de saúde do idoso.